Australia Day or Invasion Day? Perspectives on the Continuing Impact of Colonialism Underlies Public Contestations Around Australia's National Day. Issue 1 (25th March 2022) - Selvanathan, Hema Preya; Jetten, Jolanda; Crimston, Charlie R.
Abstract : The ways in which collective memories are constructed in the present is important in explaining how people choose to commemorate their nation's history. The present research focused on the context of Australia Day, a controversial national holiday that falls on January 26, which is a date that marks the beginning of colonization. We conducted field surveys of community members participating in an Invasion Day protest pushing for Indigenous rights ( n = 219) and community members enjoying the public holiday in a public park ( n = 174). We found that greater recognition of colonial history explained protesters' (vs. nonprotesters') greater support for changing the date of Australia Day. Further, protesters' lower levels of perceived continuity and higher levels of desired continuity of First Australian culture was linked to greater support for changing the date of Australia Day compared to the nonprotesters. These findings suggest that creating consensus over contested collective memories of a nation's history requires greater recognition of the ongoing impact of past atrocities.